Improving provision of family planning among pastoralists in Kenya: Perspectives from health care providers, community and religious leaders. Issue 8 (3rd August 2022) - Kenny, Leah; Bhatia, Amiya; Lokot, Michelle; Hassan, Rahma; Hussein Aden, Abdullahi; Muriuki, Angela; Ahmed Osman, Ibrahim; Kanyuuru, Lynn; Pryor, Shannon; Bacchus, Loraine J.; Cislaghi, Beniamino; Hossain, Mazeda
ABSTRACT: There exist significant inequities in access to family planning (FP) in Kenya, particularly for nomadic and semi-nomadic pastoralists. Health care providers (HCP), are key in delivering FP services. Community leaders and religious leaders are also key influencers in women's decisions to use FP. We found limited research exploring the perspectives of both HCPs and these local leaders in this context. We conducted semi-structured interviews with HCPs ( n =4) working in facilities in Wajir and Mandera, and community leaders ( n =4) and religious leaders ( n =4) from the nomadic and semi-nomadic populations the facilities serve. We conducted deductive and inductive thematic analysis. Three overarching themes emerged: perception of FP as a health priority, explanations for low FP use, and recommendations to improve access. Four overlapping sub-themes explained low FP use: desire for large families, tension in FP decision-making, religion and culture, and fears about FP. Providers were from different socio-demographic backgrounds to the communities they served, who faced structural marginalisation from health and other services. Programmes to improve FP access should be delivered alongside interventions targeting the immediate health concerns of pastoralist communities, incorporating structural changes. HCPs that are aware of religious and cultural reasons for non-use, play a key role in improving access.